1928-LB: Feasibility of Calibration-Free Intradermal Glucose Monitoring Using a Sensor Microarray - CHRISTIANSEN, MARK P.; BHAVARAJU, NARESH C.; GOTTLIEB, REBECCA; CAMPBELL, ALAN; SATTAYASAMITSATHIT, SIRILAK; BRISTER, MARK C.; NOGUEIRA, KEITH; VANDENBERG, AMY L.; YANG, RICH; TANGNEY, JARED R. (Diabetes (New York, N.Y.), 2024)
Introduction: Subcutaneous glucose sensors using introducer needles have been well characterized. Robust microsensors are required for a less invasive approach, accessing interstitial glucose in the dermis. Advancements in semiconductor manufacturing have facilitated new sensing technologies using arrays of silicon microsensors on a wearable patch without introducer needles. Several independent electrodes on the microarray chip support redundancy and reliability. The objective of this study was to evaluate the performance of a calibration-free, intradermal glucose sensor, compared to a gold standard. Methods: A 5-day study was conducted at two US sites evaluating the device in persons with Diabetes. Intradermal glucose sensors were placed on the volar forearm or upper arm. All subjects participated in one clinic day on Day 1, 3, or 5 of wear. Venous blood was obtained every 15 minutes for 8 hours and analyzed with the YSI (YSI Inc, Yellow Springs, Ohio) 2300 Stat Plus. A prospective, calibration-free algorithm was used. Results: 19 subjects with Type 1 diabetes ages 19 to 70 were studied. Mean Absolute Relative Difference (MARD) was 10.1% compared to YSI (n=388). 83.2% of paired points were within 20% of YSI and 100% were within Clark Error Grid A+B regions. Conclusion: The intradermal glucose sensor demonstrated accurate tracking and trending of glucose levels compared to the gold standard laboratory analyzer.